2008
DOI: 10.1007/s10958-008-0045-9
|View full text |Cite
|
Sign up to set email alerts
|

Elementary equivalence of the semigroup of invertible matrices with nonnegative elements

Abstract: Let R be a linearly ordered ring with 1/2, G n (R) (n ≥ 3) be the subsemigroup of GL n (R) consisting of all matrices with nonnegative elements. In [1], there is a description of all automorphisms of the semigroup G n (R) in the case where R is a skewfield and n ≥ 2. In [2], there is a description of all automorphisms of the semigroup G n (R) for the case where R is an arbitrary linearly ordered ring with 1/2 and n ≥ 3. In this paper, we classify semigroups G n (R) up to elementary equivalence.Two models U 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…In [3], E. I. Bunina and A. V. Mikhalev described all automorphisms of the subsemigroup G n (R), where R is a linearly ordered associative ring with 1/2 and n ≥ 3. In [2], Bunina and Mikhalev found necessary and sufficient conditions for these semigroups to be elementarily equivalent. In [4], E. I. Bunina and P. P. Semenov described the automorphisms of the subsemigroup of the invertible nonnegative matrices of order at least 2 over commutative partially-ordered rings with 1/2.…”
Section: Introductionmentioning
confidence: 99%
“…In [3], E. I. Bunina and A. V. Mikhalev described all automorphisms of the subsemigroup G n (R), where R is a linearly ordered associative ring with 1/2 and n ≥ 3. In [2], Bunina and Mikhalev found necessary and sufficient conditions for these semigroups to be elementarily equivalent. In [4], E. I. Bunina and P. P. Semenov described the automorphisms of the subsemigroup of the invertible nonnegative matrices of order at least 2 over commutative partially-ordered rings with 1/2.…”
Section: Introductionmentioning
confidence: 99%
“…In [2], E. I. Bunina and A. V. Mikhalev described all restrictions of automorphisms of G n (R) to GE + n (R) in the case of arbitrary linearly ordered associative rings R with 1/2, n ≥ 3. In [3], E. I. Bunina and A. V. Mikhalev described necessary and sufficient conditions for semigroups considered in [2] to be elementarily equivalent. In [4], E. I. Bunina and P. P. Semenov described automorphisms of G n (R) in the case of commutative partially ordered rings R with 1/2, and in [5] the same authors found necessary and sufficient conditions for semigroups considered above to be elementarily equivalent.…”
Section: Introductionmentioning
confidence: 99%
“…В работе [2] Е. И. Бунина и А. В. Михалёв описали все автоморфизмы полугруппы G n (R), если R -произвольное линейно упорядоченное ассоциативное кольцо с 1/2, n 3. В работе [3] Е. И. Бунина и А. В. Михалёв нашли необходимые и достаточные условия для того, чтобы эти полугруппы были элементарно эквивалентны. В работе [4] Е. И. Бунина и П. П. Семёнов описали автоморфизмы полугруппы обратимых неотрицательных матриц порядка > 2 над коммутативными частично упорядоченными кольцами с обратимой двойкой, а в работе [5] нашли необходимые и достаточные условия для их элементарной эквивалентности.…”
unclassified
“…Мы знаем, что B 1,2 коммутирует со всеми матрицами подстановок, не сдвигающих первые два элемента. Из этого получим, что a 3 3,3 . Отсюда следует, что все слагаемые правой части неравенства (14), не задействованные в выписанных только что неравенствах, должны быть равны нулю.…”
unclassified